THE POLITICS OF HALAL LABEL: BETWEEN ECONOMIC PIETY AND RELIGIOUS AMBIGUITY - Mokhamad Zainal Anwar; Yuyun Sunesti; Ihsan Ihsan (UIN Raden Mas Said Surakarta, 2020)
The use of the ‘halal’ label was expanded. Label, which is originally shown on food and beverage products only, but currently also shown on non-food and beverage products, such as tissue, pan, and refrigerator. It is a phenomenon of halalization; an expansion of halal label for the product consumed by the Muslim community. Based on the qualitative method, the results of this study show that the Millennial Muslim generation’s understanding of halal is varying and affected by varying sources of knowledge and internet use. Knowledge source was no longer lies on Kiai/Ustadz only, but also on searching engine available in cyberspace. Social media and the internet also become media used by millennial Muslim generation to search for information on the product’s rightfulness. Millennial Muslim generation just wants to use a product with a halal label, and an affordable price. If it is unaffordable, they will choose other affordable products volitionally despite no halal label. The contestation in selecting and non-selecting the halal label shows the existence of interests and authority for millennial Muslim generation. This what is called the politics of the halal label.